1987
DOI: 10.1530/jrf.0.0800589
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in testicular contents and plasma concentrations of androgens in the desert gerbil (Gerbillus gerbillus)

Abstract: Gerbils were caught in the Béni-Abbès area (Algeria). Testicular endocrine activity was highest in spring (testicular wt 298 +/- 10 mg; seminal vesicle wt 603 +/- 62 mg; testicular testosterone and androstenedione content 9.2 +/- 1.7 and 0.5 +/- 0.1 ng/testis; plasma testosterone 832 +/- 200 pg/ml). Values decreased in summer, were lowest in late summer and in autumn (84 +/- 17 mg; 40 +/- 14 mg; 0.20 +/- 0.06 and 0.02 +/- 0.01 ng/testis; 228 +/- 54 pg/ml, respectively) and increased again in winter (December-J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…Although, reproduction and mobility are generally considered to be related to trophic factors in mammals with short life-spans living in low latitudes (review in Bronson 1989), our results support some suggestions that non-trophic factors play a role in regulating these functions in Gerbillus gerbillus (Khammar and Brudieux 1987), Psammomys obesus (Kammar and Brudieux 1986) and others (Happold 1983). To summarize our results : (1) except for A. niloticus which presents a short sexual rest period induced by non-trophic factors during the second half of the rainy season, water metabolism, mobility and reproduction are not seasonal in rodents (A. niloticus and M. hnbeni) which experience a constantly rich diet (UH); (2) when rodents (A. niloticus) experience a constantly rich diet but face a flooding period (FH), water metabolism remains related to food intake, but mobility and reproduction become seasonal: a dispersion period and a sexual rest period, both induced by non-trophic factors, appear before and remain until the end of the flooding period; (3) when rodents (T. gracilis and M. erythroleucus in SH) experience marked seasonal changes in their diet with a rich-food period twice as long as the poor-food period, water metabolism, mobility and reproduction become seasonal: the dispersion period and the sexual rest period, are both related to a decrease of water metabolism, while the reproduction period and the sedentarisation period are both related to an increase in water metabolism ; non-trophic factors exert a stimulating effect on reproduction and sedentarization only in T. gracilis (which may explain why sedentarisation and reproduction appear two months earlier than in M. erythroleucus); (4) when rodents (G. nigeriae in AH) experience very marked seasonal changes in their diet with a poor-food period twice as long as the richfood period, water metabolism, mobility and reproduction become seasonal: if the dispersion period and the sexual rest period are both related to a reduction in water metabolism, the reproduction period and the complex sedentarisation period (PE, estivation, sedentarisation) are both related to non-trophic factors.…”
Section: Life Cycle Of Sahelian Rodentssupporting
confidence: 85%
“…Although, reproduction and mobility are generally considered to be related to trophic factors in mammals with short life-spans living in low latitudes (review in Bronson 1989), our results support some suggestions that non-trophic factors play a role in regulating these functions in Gerbillus gerbillus (Khammar and Brudieux 1987), Psammomys obesus (Kammar and Brudieux 1986) and others (Happold 1983). To summarize our results : (1) except for A. niloticus which presents a short sexual rest period induced by non-trophic factors during the second half of the rainy season, water metabolism, mobility and reproduction are not seasonal in rodents (A. niloticus and M. hnbeni) which experience a constantly rich diet (UH); (2) when rodents (A. niloticus) experience a constantly rich diet but face a flooding period (FH), water metabolism remains related to food intake, but mobility and reproduction become seasonal: a dispersion period and a sexual rest period, both induced by non-trophic factors, appear before and remain until the end of the flooding period; (3) when rodents (T. gracilis and M. erythroleucus in SH) experience marked seasonal changes in their diet with a rich-food period twice as long as the poor-food period, water metabolism, mobility and reproduction become seasonal: the dispersion period and the sexual rest period, are both related to a decrease of water metabolism, while the reproduction period and the sedentarisation period are both related to an increase in water metabolism ; non-trophic factors exert a stimulating effect on reproduction and sedentarization only in T. gracilis (which may explain why sedentarisation and reproduction appear two months earlier than in M. erythroleucus); (4) when rodents (G. nigeriae in AH) experience very marked seasonal changes in their diet with a poor-food period twice as long as the richfood period, water metabolism, mobility and reproduction become seasonal: if the dispersion period and the sexual rest period are both related to a reduction in water metabolism, the reproduction period and the complex sedentarisation period (PE, estivation, sedentarisation) are both related to non-trophic factors.…”
Section: Life Cycle Of Sahelian Rodentssupporting
confidence: 85%
“…8E). Although photoperiod is not generally considered to be a breeding synchronizer in mammals with short life-spans living at low latitudes (see review in Bronson 1989), it has been suggested that it plays a role in regulating reproduction in the African rodents Gerhillus gerhillus (Klein et al 1975;Khammar et Brudieux 1987), Psammomys obesus (Khammar and Brudieux 1986), and others (Happold 1983). The results obtained here support the role of photoperiod in terminating reproduction in A. n. solatus, but the triggering of this activity must depend on other gonadostimulatory factors.…”
Section: Fig 6 Seasonal Variations (January To December) In Testis mentioning
confidence: 99%
“…Testicular endocrine activity has been studied in this respect only in the sand rat (Psammomys obesus) and desert gerbil (Gerbillus gerbillus). These studies show that in the sand rat the onset of testicular endocrine activity is concomitant with the highest temperature and decreasing daylength (summer) (Khammar & Brudieux, 1986), but with the lowest temperature and increasing daylength (winter) in the desert gerbil (Khammar & Brudieux, 1987). The existence of a circadian rhythm of photosensitivity implicating photoperiodism in the regu¬ lation of sexual activity has been demonstrated in six species of Sahelian rodents in northern Burkina Faso (Sicard et ai, 1988).…”
Section: Introductionmentioning
confidence: 95%